Average Error: 0.7 → 0
Time: 15.1s
Precision: 64
• ## could not determine a ground truth for program body (more)

1. x = 1.3100436170095023e+65
$e^{x} \cdot e^{\left(-2\right) \cdot x}$
$e^{x - 2 \cdot x}$
e^{x} \cdot e^{\left(-2\right) \cdot x}
e^{x - 2 \cdot x}
double f(double x) {
double r1631600 = x;
double r1631601 = exp(r1631600);
double r1631602 = 2.0;
double r1631603 = -r1631602;
double r1631604 = r1631603 * r1631600;
double r1631605 = exp(r1631604);
double r1631606 = r1631601 * r1631605;
return r1631606;
}


double f(double x) {
double r1631607 = x;
double r1631608 = 2.0;
double r1631609 = r1631608 * r1631607;
double r1631610 = r1631607 - r1631609;
double r1631611 = exp(r1631610);
return r1631611;
}



# Try it out

Results

 In Out
Enter valid numbers for all inputs

# Derivation

1. Initial program 0.7

$e^{x} \cdot e^{\left(-2\right) \cdot x}$
2. Simplified0

$\leadsto \color{blue}{e^{x - 2 \cdot x}}$
3. Final simplification0

$\leadsto e^{x - 2 \cdot x}$

# Reproduce

herbie shell --seed 1
(FPCore (x)
:name "exp(x)*exp(-2*x)"
:precision binary64
(* (exp x) (exp (* (- 2) x))))